2015
DOI: 10.1159/000438756
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxytocin Levels in Untreated Adult Obsessive-Compulsive Disorder Patients

Abstract: Background and Aim: Given the paucity of information on the possible role of oxytocin (OT) in the pathophysiology of obsessive-compulsive disorder (OCD), our study aimed at evaluating plasma OT levels in a group of 44 OCD outpatients, as compared with a similar group of healthy control subjects. At the same time, the relationships between OT and clinical features and romantic attachment characteristics were examined as well. Methods: Diagnosis was assessed according to DSM-IV-TR criteria, while the OCD severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…Indeed, a properly regulated OT system has been suggested to enhance resilience and to act as a hurdle against the development of mental disorders and/or substance abuse [49, 50]. Accumulating evidence suggests a role for OT in the pathophysiology of different psychopathological conditions, mainly in those characterized by social and emotional deficits [3, 29, 30, 51, 52], such as depression [53-56], social phobia [57], anxiety disorders [3], autism spectrum disorders [58, 59], OCD [60, 61], post traumatic stress disorders [9], and other conditions [61-63] almost all characterized by a female preponderance [64, 65]. Again, sex-related OT differences have been related to emotional distress [28, 66] and to the anxiety of a love relationship [36, 67].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a properly regulated OT system has been suggested to enhance resilience and to act as a hurdle against the development of mental disorders and/or substance abuse [49, 50]. Accumulating evidence suggests a role for OT in the pathophysiology of different psychopathological conditions, mainly in those characterized by social and emotional deficits [3, 29, 30, 51, 52], such as depression [53-56], social phobia [57], anxiety disorders [3], autism spectrum disorders [58, 59], OCD [60, 61], post traumatic stress disorders [9], and other conditions [61-63] almost all characterized by a female preponderance [64, 65]. Again, sex-related OT differences have been related to emotional distress [28, 66] and to the anxiety of a love relationship [36, 67].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, oxytocin injection into the central nucleus of the amygdala has been shown to induce hypergrooming, assumed to reflect OCD-related behavior [14]. Accordingly, elevated plasma and cerebrospinal fluid oxytocin levels were found in OCD [15,16]. On an epigenetic level, increased OXTR exon III methylation was discerned in OCD patients compared to healthy controls [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the oxytocin signalling pathway could explain findings by Chatzittofis et al, who observed HPA axis dysregulation in men with hypersexual disorder [3]. Furthermore, studies indicate that oxytocin may be involved in the pathophysiology of obsessive-compulsive disorder [63]. The interaction of oxytocin with the dopamine system, the HPA-axis and the immune system led to the postulation that individual differences in oxytocin levels are impacting addiction vulnerability [64].…”
Section: Discussionmentioning
confidence: 99%